2003
DOI: 10.1128/jvi.77.9.5167-5177.2003
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the Human Papillomavirus Type 16 Late Negative Regulatory Element Is Partly due to Four Weak Consensus 5′ Splice Sites That Bind a U1 snRNP-Like Complex

Abstract: The human papillomavirus (HPV) life cycle is tightly linked to differentiation of the squamous epithelia that it infects. Capsid proteins, and hence mature virions, are produced in the outermost layer of differentiated cells. As late gene transcripts are produced in the lower layers, posttranscriptional mechanisms likely prevent capsid protein production in less differentiated cells. For HPV type 16 (HPV-16), a 79-nucleotide (nt) negative regulatory element (NRE) inhibits gene expression in basal epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 34 publications
(39 reference statements)
1
55
0
Order By: Relevance
“…1B. The mutated HPV16 U1 binding sites are identical to a previously published mutation (21,27) that inactivates this element because it inactivates base pairing to U1 snRNP. In contrast there is no published fine-scale substitution mutant of the GRE.…”
Section: Analysis Of the Hpv16 Nrementioning
confidence: 68%
See 2 more Smart Citations
“…1B. The mutated HPV16 U1 binding sites are identical to a previously published mutation (21,27) that inactivates this element because it inactivates base pairing to U1 snRNP. In contrast there is no published fine-scale substitution mutant of the GRE.…”
Section: Analysis Of the Hpv16 Nrementioning
confidence: 68%
“…In reporter plasmids where the 3Ј-UTR and sequences past the poly(A) site are derived from the corresponding HPV16 sequences, expression of the reporter is low. Deletion of the NRE but not other parts of the 3Ј-UTR resulted in a large increase in expression ranging from 40-to 100-fold depending on the transfection conditions and cell types used (18,21,26,27). As diagrammed in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first example of an endogenous cellular gene having a functional U1 site. Up to now, only two types of U1 sites had been reported: U1 sites in papillomaviruses (Furth et al 1994;Cumming et al 2003) and artificial U1 sites used to silence expression of reporter and specific endogenous genes (Beckley et al 2001, Fortes et al 2003. Prior work from multiple labs showed that these U1 sites use the same mechanism, namely inhibition of pre-mRNA maturation by inhibition of nuclear polyadenylation resulting in lower mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…To date, naturally existing U1 sites have only been reported in papillomaviruses (Furth et al 1994;Cumming et al 2003) with no functional ones being reported in cellular genes. Here, we use bioinformatics and a reporter gene and in vitro polyadenylation assays to identify and characterize a U1 site in the terminal exon of the human U1A gene.…”
Section: Introductionmentioning
confidence: 99%